Calling memory into place - Apel, Dora, 1952- (New Brunswick : Rutgers University Press, 2020)
"Calling Memory into Place offers a unique mix of cultural and political critique combined with memoir and family history in order to explore issues of cultural memory and identity. Focusing on the overlapping themes of intergenerational Holocaust trauma, racial violence, and gendered experience, Apel shows how cultural representations intersect with the experience of place and embodied knowledge as important ways of knowing. By investigating the relations among place, memory, and identity, this study shines a light on the dynamic nature of memory as it crosses geography and generations, demonstrating how cultural narratives rewrite an understanding of the self as well as group and national identity. In ten essays, Apel examines the ongoing construction of memory through memorials, photographs, artworks, and personal stories that open up a process of "unforgetting"--Remembering what was formerly considered unworthy of being remembered or reinterpreting the meaning of the past. These essays explore the protests in Ferguson following the police killing of Michael Brown, the controversy over a painting of Emmett Till in the Whitney Biennial, and debates about a national lynching memorial in Montgomery, Alabama, as well as the contested politics of place during a visit to Israel/Palestine, a return to the hometown in Poland of the author's Holocaust survivor parents, a memorial for philosopher Walter Benjamin in Spain, and the constructive uses of inherited trauma in the author's breast cancer treatment and struggle for self-advocacy in the patriarchal medical institution, among other topics. By shifting between the scholarly, the personal, and the visual as different ways of knowing, these essays perform in practice an attention to the political and affective dimensions of trauma, memory, and place, demonstrating the need to remember the repressed and marginalized voices of the past in the struggle for equality and social justice in the present"--
Cover -- Title Page -- Copyright -- Dedication -- Contents -- Introduction -- PART I: PASSAGES AND STREETS. 1. A memorial for Walter Benjamin -- 2. "Hands up, don't shoot" -- PART II: MEMORIALS AND MUSEUMS. 3. Why we need a national lynching memorial -- 4. "Let the world see what I've seen -- PART III: HOMETOWNS AND HOMELANDS. 5. Seeing what can no longer be seen -- 6. Borders and walls -- PART IV: HOSPITALS AND CEMETERIES. 7. Sprung from the head -- 8. Parallel universes -- PART V: BODY AND MIND. 9. Reclaiming the self -- 10. The care of others -- Conclusion -- Acknowledgments -- Notes -- Selected bibliography -- Index -- About the author.
Includes bibliographical references and index.
Print version record; online resource viewed February 17, 2021.
In English.
eBooks on EBSCOhost
Keywords: Collective memory; Memory -- Political aspects; Memory -- Social aspects; Memory -- Psychological aspects; Mémoire collective; ART / General; Collective memory; Memory -- Political aspects; Memory -- Psychological aspects; Memory -- Social aspects; Memory, Traumatic Memory, Photographs, Artworks, Autobiographies, Stories, Unforgetting, Perspective, Holocaust, Survivors, Intersectionality, Racism, Antisemitism, Sexism, Trauma, History, Identity, Geography, Generations, Essays, Visuals, Personal Stories; Electronic books